Recurrent venous thromboembolism and clot distribution in COVID-19 infection: A review by variant type - Laura Saldivar; Tannaz Rajabi; Wei Li; Samia Lopa; Dominick Roto; Jeffrey Bruckel; Daniel Lachant; Mark Marinescu (PLoS ONE, 2025)
Research question Do PE distribution and rates of recurrent VTE differ between COVID-19 (CAPE) and non-COVID-19 (NCAPE) patients and among COVID-19 variants? Study design and methods A single-center retrospective chart review of 547 patients with PE admitted from January 2020-October 2022 was conducted. 470 patients did not have COVID-19 infection on admission. 77 patients had COVID-19 infection with 17, 27, and 33 admissions occurring during Alpha, Delta, and Omicron predominance, respectively. Imaging reports, follow-up, and recurrent VTE incidence were extracted. Central clot was defined as saddle or mainstem PE. Clot distribution was classified as central, peripheral, or both. Recurrent VTE was examined at 3 and 6 months. Results NCAPE and CAPE patients had similar patterns of clot distribution overall (P = 0.34, 0.48, & 0.82 for central, peripheral, and both, respectively). Of CAPE patients with solely peripheral PE distribution (N = 49), Omicron comprised 78.8% (N = 26, P = 0.01). Recurrent VTE occurred in 45 patients. The cumulative proportion of recurrent VTE or death did not differ significantly by COVID-19 status (P = 0.12). Conclusions: COVID-19 infection is associated with VTE events which appear to vary in frequency and location among the different variants (Alpha, Omicron, and Delta). VTE risk is highest in the 3 months following COVID-19 infection. Recurrent rate of VTE is similar between patients with COVID-19-associated and non-COVID-19-associated PE. The VTE risk and clot distribution of COVID-19 is evolving over the years as the virus becomes endemic in the United States and warrants further study.